Determinants of Financial Market Spillovers : The Role of Portfolio Diversification, Trade, Home Bias, and Concentration - Shinagawa, Yoko (IMF Working Papers; Working Paper ;, 2014)
This paper defines financial market spillovers as the comovement between two countries' financial markets and analyzes financial market spillovers over the period 2001-12 through four channels: bilateral portfolio investment, bilateral trade, home bias, and country concentration. The paper finds that, if a country has a large amount of bilateral portfolio exposure in another country, these two countries' comovement of bond yields are large. Also, countries' geographical preferences impact financial spillovers; if a country has a stronger home bias, the country could have less spillovers from foreign financial markets. A policy implication from this result is that, if countries become less home-biased and have a greater amount of portfolio investment assets, they should strengthen prudential regulations to mitigate against rising risks of financial spillovers (or risk greater volatility owing to comovement with foreign markets).